Obligation of Service Toward Wife and Children According to Legal and Islamic Law - Ade Jamarudin; Muh Said; Syafi’ah; Ahmad Firman Hidayatullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Marriage is a form of legal action between husband and wife. Marriage is not only interpreted to realize worship to Allah alone, with the existence of a marriage, it will cause civil law consequences between the two. Here there are arrangements regarding the rights and obligations of each husband and wife, the husband is the heart of life in the family where it is the husband who has the advantage to lead a family compared to a wife who looks after assets and takes care of her husband and children, one of the responsibilities of a husband is in the wheels of the economy. The condition of the convicts who are in the Correctional Institution only participates in coaching program activities, there is no extra effort that must be made by convicts in fulfilling their own living because the independence coaching that is carried out is only limited to training. However, it is different from the situation when the prison itself has adequate facilities so that the convicts can work or manage in agriculture, animal husbandry or home industry. The research method used is Juridical-Dogmatic or Normative-Juridical. The results of the research conducted show that inmates who are in Correctional Institutions cannot provide a living for their families, but there are efforts they can make, namely first entrusting their wives and children to their families so that their dependents become debts, secondly by leaving a business for their children and wives before they are in the penitentiary.